EFEKTIVITAS ZAKAT PRODUKTIF DAN KUALITAS PENDAMPINGAN TERHADAP KEMANDIRIAN EKONOMI MUSTAHIK DI KABUPATEN CIAMIS - Kikin Mutakin; Acim Acim; Akmaludin Akmaludin (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2026)
This study aims to analyze and empirically test the effect of the effectiveness of productive zakat and the quality of mentoring, both partially and simultaneously, on the economic independence of mustahik in Ciamis Regency. The research approach used is quantitative with a causal associative method. The population in this study were mustahik recipients of the productive zakat program in Ciamis Regency with a sample of 100 respondents determined using the Slovin formula and purposive sampling technique. Data collection was carried out by distributing questionnaires with a Likert scale. Data analysis was carried out using classical assumption tests, multiple linear regression analysis, and hypothesis testing with the help of IBM SPSS software. The results of the study indicate that partially the effectiveness of productive zakat has a positive and significant effect on the economic independence of mustahik (t = 4.420; sig = 0.000). The quality of mentoring is also proven to have a positive and significant effect on the economic independence of mustahik (t = 7.102; sig = 0.000). Simultaneously, the effectiveness of productive zakat and the quality of mentoring significantly influence the economic independence of mustahik (F = 35.487; sig = 0.000). The R Square value of 0.423 indicates that the contribution of the effectiveness of productive zakat and the quality of mentoring in explaining the variation in economic independence of mustahik is 42.3%, while the remaining 57.7% is influenced by other factors outside the research model. The conclusion of this study confirms that the success of the mustahik economic empowerment program is not only determined by the effectiveness of productive zakat distribution, but is also greatly influenced by the quality of the mentoring provided. Therefore, the integration between appropriate business capital assistance and quality mentoring is an important factor in encouraging the realization of economic independence of mustahik in Ciamis Regency.